Morphological spectrum of peripheral nerve sheath tumors: A series of 126 cases - Gabhane Sushma; Kotwal Mrunamayi; Bobhate Sudhakar (Wolters Kluwer Medknow Publications, 2009)
By convention, soft tissue tumors include the peripheral nerve sheath tumor (PNST) although they arise from neuroectoderm. PNSTs display a wide spectrum of morphology and biological behavior. Malignant transformation in benign tumors, especially neurofibroma, is an acknowledged phenomenon.This article describes clinico-pathological features of 126 PNSTs with their morphological variants and those associated with neurofibromatosis 1 (NF1) encountered in a single center over a 6-year period. Benign PNSTs were more common [118 (93.65%)] when compared with their malignant counterparts [8 (6.34%)]. Histological variants including plexiform schwannomas and diffuse, plexiform and pigmented forms of neurofibromas, though rare, were observed. Eleven (8.73%) patients with NF1 showed a strong association with plexiform neurofibroma. A malignant transformation in pre-existing neurofibroma was seen in 1 patient with NF1. This series highlights the clinico-pathological spectrum of PNSTs, their morphological variants and the incidence of associated NF1. The importance of detecting plexiform variants lies in their vastly different prognostic implications particularly when occurring in the setting of NF1